2019
DOI: 10.1155/2019/7278531
|View full text |Cite
|
Sign up to set email alerts
|

Robust H Consensus Control for Linear Discrete-Time Swarm Systems with Parameter Uncertainties and Time-Varying Delays

Abstract: Robust H∞ consensus control problems of linear swarm systems with parameter uncertainties and time-varying delays are investigated. In this literature, a linear consensus protocol for high-order discrete-time swarm systems is proposed. Firstly, the robust H∞ consensus control problem of discrete-time swarm systems is transformed into a robust H∞ control problem of a set of independent uncertain systems. Secondly, sufficient linear matrix inequality conditions for robust H∞ consensus analysis of discrete-time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, due to the complex composition of lumped disturbance and the mechanical characteristics of the AMB, modeling the lumped disturbance in the imaging phase is a challenging problem. Furthermore, plenty of related research works have focused on controller design with disturbance, uncertainty, and nonlinearity, including the model predictive control [9], the robust H-infinity control [10,11], and the active disturbance rejection control [12,13]. Moreover, the sliding mode control (SMC) has been widely used in satellite attitude control due to its high accuracy and strong robustness against disturbances [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complex composition of lumped disturbance and the mechanical characteristics of the AMB, modeling the lumped disturbance in the imaging phase is a challenging problem. Furthermore, plenty of related research works have focused on controller design with disturbance, uncertainty, and nonlinearity, including the model predictive control [9], the robust H-infinity control [10,11], and the active disturbance rejection control [12,13]. Moreover, the sliding mode control (SMC) has been widely used in satellite attitude control due to its high accuracy and strong robustness against disturbances [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Some related works have been investigated by many researchers. [3][4][5][6][7][8][9][10][11][12] For example, Reference 3 presented a solution to the leader-following consensus problem of linear multi-agent systems with modeling uncertainties by using the robust optimal control theory. Reference 4 dealt with robust H ∞ consensus control problem for linear discrete-time MASs with parameter uncertainties and time-varying delays.…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative control of MAS originated from bioscience, where many researchers aroused great interest in birds, bees, and fishes in nature. Many scholars found that the above cooperative behavior among agents is based on the swarm consensus [10][11][12][13][14][15][16][17], and all agents could perform tasks that cannot be achieved by a single one as a formation structure. e formation control, as a fundamental and key issue of cooperative control, refers to a team of interacting agents to perform complex tasks together in a certain geometric structure, which is applied to many fields, such as networking system of satellite clusters, movements of mobile robotics [18,19], cooperative attack of multiple missiles [20], and unmanned aerial vehicle formations [21,22].…”
Section: Introductionmentioning
confidence: 99%